HAZARDS AND SAFETY IN PROCESS INDUSTRIES case studies. - Purkait, Mihir Kumar; Mondal, Piyal; Changmai, Murchana; Volli, Vikranth; Shu, Chi-Min ([S.l.] : CRC PRESS, 2021)
Safety in process industries is of utmost necessity to ensure protection from hazards. The aim of this book is to elucidate the hazards and preventive measures for a few of such specific industrial processes. Starting with overview of the prevalent industrial accidents, types of hazards and safety provisions, the book contains nineteen chapters with each one of them consisting of a unique case study comprising of basic causes, results and discussion, and protective measures to be adopted to overcome such situation. Topics covered include caprolactam storage tank accident, fire explosion accident caused by static electricity, and human factors risk and management in process safety and so forth. Aimed at researchers, professionals, graduate students in Chemical Engineering, Safety Management, Risk Assessment, Chemical Process Safety, this book: Provides exhaustive coverage of industrial case studies on their hazards and safety issues in the process industry set-up. Includes quantitative discussion on new and existing technologies and methodologies. Explores high quality descriptive and quantified data for better visualization of each chapter. Gives detailed description on various industrial accidents, their related consequences and available safety/preventive measures. Discusses preventive measures taken by world class industries in their production plants.
OCLC-licensed vendor bibliographic record.
Keywords: Chemical processes -- Safety measures; Industrial safety; Hazardous substances -- Safety measures; SCIENCE / Chemistry / Industrial & Technical; TECHNOLOGY / Engineering / Industrial; TECHNOLOGY / Industrial Health & Safety